Impact of Knowledge Management on Industrial Performance: Evidence from Nepalese Industrial Estate (Quest Journal of Management and Social Sciences, 2024)
Background: Knowledge management is crucial for industrial success and continuity, playing a vital role in the management of industries. Effective knowledge management can lead to improved performance and competitive advantage.Objective: This study aims to understand the impact of knowledge management on industrial performance in the Kathmandu Valley, Nepal, focusing on both tacit and explicit knowledge.Method: The study is grounded in the Organizational Knowledge Creation Theory and follows an explanatory research design. A total of 173 managers from various industries within Kathmandu Valley were interviewed using a structured questionnaire facilitated by the Kobo Toolbox. The data were analyzed using Structural Equation Modeling (SEM) with SPSS and AMOS software to examine the relationship between knowledge management practices and industrial performance.Result: The findings reveal that both tacit and explicit knowledge have a significant positive impact on organizational performance. The ability to rapidly gather, document, and share information within an organization enhances industrial performance.Conclusion: The study concludes that effective knowledge management is essential for maximizing industrial performance in Nepalese industrial estates. The emphasis on a culture of information documentation and sharing within organizations can lead to substantial performance improvements.Paper Types: Research PaperKey Words: Knowledge management, organizational performance, industrial estates, SEM, Kathmandu ValleyJEL Classification: D83, L25, P27